Sartre’s theory of temporality in Being and Nothingness in Anglo-American academic discourse (Colloquia Comparativa Litterarum, 2025)
The study “Sartre’s Theory of Temporality in Being and Nothingness in Anglo-American Academic Discourse” presents in some detail Sartre’s ideas of time in his magnum opus Being and Nothingness (L’Être et le néant, 1943). The topic is dictated by the fact that these ideas have not been fully discussed by original philosophical literature in Anglo-American academia (English translations from French are not considered). The essay details three topics. The first, introductory part outlines the way Sartre’s theory of temporality in Being and Nothingness has or, rather, has not been fully analyzed in the specialized and popular philosophical literature in English. The overview covers some 65 titles on Sartre, existentialism, and phenomenology. The second section delineates Sartre’s theory of temporality in Being and Nothingness. The final part speaks of Sartre’s ideas of time in his literary criticism, namely, in his essay “On The Sound and the Fury: Time in the Work of Faulkner.”
Keywords: Jean-Paul Sartre; time; Being and Nothingness; L’Être et le néant; existentialism; phenomenology; Sartre in Anglo-American academia; critical theory